Transient Behavior of the M /G / m and M /G/oo Systems - Ferreira, M. A. M.; Andrade, M. A. P. (EasyChair Preprint Nº 7934, 2025)
It is intended, in this work, to present an approximation process of the M / G / m transient behaviour, X(t), since for it there is not a known expression. It is called diffusion process and the results obtained are in (1-2). The numerical results obtained by Choi and Shin, see (1), are compared with the ones given by the analogous expressions for the M/G/oo system, see (3). It is concluded that this system can approximate quite well the M / G / m system transient behaviour